Manual para el diseño y construcción de piscinas residenciales y semideportivas - Mora-Fonseca, Gustavo (Instituto Tecnológico de Costa Rica, 2008)
The next work develops the research from which was obtained the Manual for design and construction of residential and semi-sport pools, built under the type of concrete masonry blocks. The document's main objective is to generate a directory of technical and practical support to users, agglomerating information, that so far was not documented. The project was developed by collecting information from leading companies in the construction and design of pool projects in Costa Rica, experienced staff, builders, architects and engineers specialists in the field. Results have been obtained related to the structural stability of the projects, architectural, electrical and mechanical design. Among others. It is concluded that the structural elements typically used meet the needs in various use cases. They also achieved economic value, thereby facilitating the design and construction of swimming pools. It was confirmed that a large amount of information about this subject pool is not documented, there is a large amount of knowledge from empirical nature.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2008.
Keywords: Manual de especificaciones; Losas de concreto; Intervención arquitectónica; Tuberías; Factor resistencia